Assembly and Function of the Lambdoid Bacteriophage Tail: Observations from φ80-Lambda Host-Range Phenotypic Mixing - Boklage, Charles E. (1973)
The host-range proteins of lambda and φ80, while differing sharply in host-receptor specificity and in sensitivity to phage-killing antiserum, can be assembled into functional phage tail structures of mixed composition.